Manuscript Sources and Medial Transfer in the Research of Early Modern Disputations: From Administration to Exchange of Knowledge - Förköli, Gábor (Renaissance and reformation, 2024)
The scholarship of early modern disputations has concentrated on printed theses, since they are one of the most common types of prints in the era. Although preserved minutes transcribing what was said while these theses were discussed are rare, this article argues that it is worth giving due consideration to such manuscript sources when it comes to researching this very topic. Endeavouring to investigate Catholic and Protestant examples from Central Europe between 1580 and 1660, I explore four areas where handwritten documents, such as university records and student notebooks, have the potential to nuance our understanding of different traditions pertaining to disputation. In comparison to the printed disputations typical for Protestant Europe, manuscripts with Catholic and Jesuit provenance reveal a different function of scholarly debates, which were less focused on the individual performance of the respondent and served more as a method of recapitulation in everyday education. Protestant examples, on the other hand, demonstrate that disputations played a distinguished role in the exchange of scientific knowledge and expertise. During the process of professors and students conveying information from their homeland to university centres and back, disputations changed medium from print to manuscript, and vice versa., La recherche sur la disputatio dans les premiers temps modernes s’est concentrée jusqu’ici sur les thèses imprimées, celles-ci comptant parmi les types d’imprimés les plus courants de l’époque. Bien qu’il nous soit resté peu de procès-verbaux rapportant les discussions autour de ces thèses, le présent article affirme qu’il convient de prêter une juste attention à ces sources manuscrites dans la recherche sur la disputatio. Sur la base d’exemples catholiques et protestants en Europe centrale de 1580 à 1660, l’auteur explore quatre domaines où des documents manuscrits, tels des archives d’universités et des carnets d’étudiants, peuvent nuancer notre conception de différentes traditions relatives à la disputatio. Contrairement aux disputationes imprimées typiques de l’Europe protestante, les manuscrits de provenance catholique et juive révèlent que les débats savants ne mettaient pas l’accent sur la performance du répondant, constituant avant tout une méthode de récapitulation pour l’instruction quotidienne. Les exemples protestants montrent en revanche que les disputationes jouaient un rôle éminent dans l’échange des connaissances et compétences scientifiques. Enfin, à mesure que professeurs et étudiants transmettaient de l’information entre leur patrie et les centres universitaires, les disputationes changeaient de médium, passant de l’imprimé au manuscrit et vice-versa.